Tooth Loss, Periodontitis, and Statins in a Population‐Based Follow‐Up Study. Issue 6 (1st June 2014) - Meisel, Peter; Kroemer, Heyo K.; Nauck, Matthias; Holtfreter, Birte; Kocher, Thomas
Abstract : Background: Statins, frequently prescribed in lipid‐lowering therapies, seem to have additional beneficial effects on periodontitis and tooth loss. If this is true, then chronic treatment with statins should also result in diminished tooth loss as a long‐term response. Methods: A 5‐year population‐based follow‐up study of tooth loss was performed comparing participants treated with statins (n = 134) with those not on the drugs (Study of Health in Pomerania). Negative binomial regression models were used to analyze the count variable of the outcome, including risk factors for tooth loss and measures of cholesterol metabolism. Results: When adjusted for age and sex, statins were associated with reduced tooth loss during the follow‐up period (incidence risk ratio [IRR] = 0.70, 95% confidence interval [CI] = 0.50 to 0.99, P = 0.04). When additionally adjusted for risk factors of periodontal breakdown, IRR was 0.72 (95% CI = 0.52 to 1.01). There was significant interaction with low‐density lipoprotein cholesterol (LDL‐c) at baseline. After stratification by LDL‐c, statins were associated with reduced tooth loss, resulting in IRR = 0.89 (95% CI = 0.44 to 1.83) and 0.64 (95% CI = 0.43 to 0.95), P = 0.03, at LDL‐c concentrations ≤100 mg/dL and >100 mg/dL (2.58 mmol/L), respectively. The data also showed reduced tooth loss associated with the 5‐year reduction in LDL‐c levels on a mmol/L basis and independently of statins (IRR = 0.87, 95% CI = 0.80 to 0.96, P = 0.004). Conclusion: Long‐term treatment with systemically administered statins may have the beneficial effect of protecting against tooth loss.